Comparison of physical fitness level among different competition categories in women's basketball: A systematic review - Adriano Vretaros (Turkish Journal of Kinesiology)
Acquiring good levels of physical fitness in women's basketball is crucial for success in this complex sport. Thus, the objective of the research is to compare the level of physical fitness in women's basketball between different competitive categories through a systematic review. For this purpose, four databases were consulted (Google Scholar, PubMed, Scielo and LILACS) in Portuguese, Spanish and/or English, in which 32 primary scientific articles were found on physical fitness in women's basketball in the competitive categories and 51 manuscripts complementary secondary about the theme. Physical fitness indicators are divided into anthropometric, metabolic and neuromuscular. Each indicator has a series of variables whose sum will allow us to understand the athlete's actual physical fitness status. The physical training of female players follows the same guidelines as male athletes, but three aspects deserve attention when prescribing programs: menstrual cycle, eating disorders and bone mineral loss. In addition, cardiovascular and neuromuscular characteristics distinguish genders and interfere with physical fitness gains. In general results, professional basketball players presented better averages in the group of indicators (63.1%), followed by formative (21.0%), college (10.5%) and semi-professional (5.26%) players. Finally, it was evident that as female players progress in chronological age, they mature biologically and acquire training support, advancing between the competitive categories. In this way, your physical fitness comes to denote improvement. However, there is a large individual biological variability that impacts the average numbers between the indicators.